From direct engagement to technical support: a programmatic evolution to improve large community health worker programs in Bihar, India - Andreea A Creanga; Aritra Das; Sridhar Srikantiah; Tanmay Mahapatra; Sunil Sonthalia; Hemant Shah; Jess Wilhelm; Christine Galavotti (BMJ Global Health)
Introduction In 2011, through a multipartner Integrated Family Health Initiative (IFHI), CARE started supporting maternal and neonatal health (MNH) improvement goals in 8 of 38 districts in Bihar, India. The programme included a frontline health worker (FHW) component offering health advice through household visits and benefited from CARE’s direct engagement during IFHI, which then evolved into statewide Technical Support Unit (TSU) to the Government of Bihar in 2014.Methods Using eight rounds of state-representative household surveys with mothers of infants aged 0–2 months (N=73 093) linked with two facility assessments conducted during 2012–2017, we assessed changes in FHW visit coverage, intensity and quality between IFHI and TSU phases. Using logistic regression models, we ascertained associations between FHW outputs and three MNH core practices: ≥3 antenatal care check-ups (ANC3+), institutional delivery and early breastfeeding initiation.Results Women’s receipt of 1+ FHW visits declined from 60.2% (IFHI phase) to 46.3% (TSU phase) in the eight IFHI districts, being below 40% statewide during the TSU phase. Despite a parallel decline in FHW visit quality measured as the number of health advice received, all three outcomes improved during the TSU versus IFHI phase in IFHI districts. We found significant positive associations between all three outcomes and receipt of 1+ FHW visits and programme phase (TSU vs IFHI) in the eight IFHI districts. During the TSU phase, receipt of 2+ FHW visits in the third trimester increased the odds of women receiving ANC3+ (adjusted OR (aOR)=1.21; 95% CI: 1.13 to 1.31), delivering in a facility (aOR=1.64; 95% CI: 1.51 to 1.77) and initiating breast feeding early (aOR=1.18; 95% CI: 1.05 to 1.18). Independent of the number and timing of FHW visits, we also found positive associations between women reporting higher than lower quality of FHW interactions and receiving outcome-specific advice and all three MNH outcomes.Conclusion Implementation of large community-based interventions under the technical support model should be continuously and strategically evaluated and adapted.